2012
DOI: 10.3390/ijms131114219
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Reactions of Flavoenzymes

Abstract: Enzymes containing flavin cofactors are predominantly involved in redox reactions in numerous cellular processes where the protein environment modulates the chemical reactivity of the flavin to either transfer one or two electrons. Some flavoenzymes catalyze reactions with no net redox change. In these reactions, the protein environment modulates the reactivity of the flavin to perform novel chemistries. Recent mechanistic and structural data supporting novel flavin functionalities in reactions catalyzed by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…The flavin-sugar adduct is important in ring opening and activation of the C1 Gal p [27]. In this process, the flavin also functions as a molecular scaffold, providing the structural constraints required for ring contraction (Scheme 2B) [31]. Formation of this intermediate made mechanistic sense and was consistent with the breaking of the anomeric bond determined from PIX studies and the lack of activity observed with the enzyme reconstituted with 5-deaza-FAD.…”
Section: Chemical Mechanisms Of Ugmmentioning
confidence: 73%
See 1 more Smart Citation
“…The flavin-sugar adduct is important in ring opening and activation of the C1 Gal p [27]. In this process, the flavin also functions as a molecular scaffold, providing the structural constraints required for ring contraction (Scheme 2B) [31]. Formation of this intermediate made mechanistic sense and was consistent with the breaking of the anomeric bond determined from PIX studies and the lack of activity observed with the enzyme reconstituted with 5-deaza-FAD.…”
Section: Chemical Mechanisms Of Ugmmentioning
confidence: 73%
“…Novel roles of flavins in noncanonical redox neutral reactions have been identified in other enzymes [31], however, UGM is the only flavoenzyme that forms a covalent intermediate by acting as a nucleophile [9, 35, 36]. …”
Section: Chemical Mechanisms Of Ugmmentioning
confidence: 99%
“…Interestingly, the flavin does not participate in a net redox reaction, rather it acts as a nucleophile that attacks the anomeric carbon atom of the substrate. UGM is thus an example of a noncanonical flavoenzyme …”
Section: Introductionmentioning
confidence: 99%
“…UGM is thus an example of a noncanonical flavoenzyme. 5 Crystal structures are available for several UGMs. The E. coli UGM structure was reported in 2001 (PDB ID 1I8T), 6 and since then several more structures of bacterial and eukaryotic UGMs have been deposited in the Protein Data Bank.…”
Section: Introductionmentioning
confidence: 99%
“…S6). Some flavoenzymes catalyze reactions with no net redox change, in which the flavin, acting either as an electron donor and nucleophile or as a base, modulates the reactivity of the protein environment to perform novel reactions (Sobrado, 2012). In the reaction catalyzed by chorismate synthase, the flavin might act as a base/H-atom abstractor for C-H bond cleavage after breakage of the C-O bond (Osborne et al, 2000).…”
Section: The Reaction Mechanismmentioning
confidence: 99%